Effects of concurrent aerobic and resistance training on vascular health in type 2 diabetes: a systematic review and meta-analysis - Chen, Shengju; Zhou, Kaixiang; Shang, Huayu; Du, Mingyang; Wu, Linfeng; Chen, Yu (Frontiers in Endocrinology, 2023)
Objective To determine the impacts of concurrent aerobic and resistance training on vascular structure (IMT) and function (PWV, FMD, NMD) in type 2 diabetes (T2D). Methods The electronic databases PubMed, Web of Science Core Collection, Cochrane Library, Embase, Scopus, CINAHL, and SPORTDiscus were systematically searched for articles on “type 2 diabetes” and “concurrent training” published from inception to August 2, 2022. We included randomized controlled trials that examined the effects of concurrent training versus passive controls on IMT, PWV, FMD and NMD in T2D. Results Ten studies were eligible, including a total of 361 participants. For IMT, concurrent training showed a slight decrease by 0.05 mm (95% CI −0.11 to 0.01, p > 0.05). concurrent training induced an overall significant improvement in FMD by 1.47% (95% CI 0.15 to 2.79, p < 0.05) and PWV by 0.66 m/s (95% CI −0.89 to −0.43, p < 0.01) in type 2 diabetics. However, concurrent training seemed to exaggerate the impaired NMD (WMD = −2.30%, 95% CI −4.02 to −0.58, p < 0.05). Conclusions Concurrent training is an effective method to improve endothelial function and artery stiffness in T2D. However, within 24 weeks concurrent training exacerbates vascular smooth muscle dysfunction. More research is needed to explore whether longer and/or higher-intensity concurrent training interventions could enhance the vascular structure and smooth muscle function in this population. Systematic review registration www.crd.york.ac.uk/PROSPERO/, identifier CRD42022350604.